Caracterização geomorfológica e do quadro físico da carta topográfica de Pitimbu-PB, 1:25.000 - Santos, Marquilene da Silva (2011)
The processes that originate the various forms of relief are not the same across the land surface. They change according to the rock nature, the geological structure, the soil cover and the climate, which, together, influence the evolution of the relief, resulting in different features. Aiming at characterizing the geomorphology and Pitimbu-PB topographic map, 1:25 000 scale, this research focuses on an analysis of the physical aspect, also considering the human influence on the relief sculpture process. Located on the southern coastline of Paraíba, the area is inserted in the geomorphologic field of the coastal tableland, called Tabuleiros Litorâneos, which are predominantly carved on poorly consolidated sediments of the Grupo Barreiras and on the coastal lowlands, called Baixada Litorânea, made of recent Quaternary deposits. The methodology was based on literature, analysis of CBERS-2B satellite images, Shuttle Radar Topographic Mission (SRTM) images, the elaboration of hypsometric, clinographic, and geomorphologic maps, land use and occupation map (with the help of SPRING, 5.03), the elaboration of topographic profiles, and field work. It was noted that there are evidences of neotectonic activity, which influence the current configuration of the Tabuleiros Litorâneos in the region. Besides several folds and faults present in Grupo Barreiras, differences were found in the altitudes of the tablelands to the north and south as well as more pronounced slopes, especially, in the cliffs and hogbacks that engrave some rivers. The drainage system also reveals a strong structural and tectonic control, with rectangular shape, rectilinear courses, asymmetric drainage and steep slant water courses. The large carvings of the valleys and the interfluvial dimension have given rise to a very dissected relief, especially in the northern portion. It was observed that the forms of occupation and land use in the area occur at odds with the current legislation, causing environmental imbalances. Considering that the human occupation of a territory is directly linked to the environmental physical conformation, any planning related to the activities undertaken in space must take into account the knowledge of the environmental characteristics, particularly, those of the relief.